2008
DOI: 10.1002/jnr.21678
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BASP1‐mediated neurite outgrowth

Abstract: The brain acid-soluble protein BASP1 (CAP-23, NAP-22) belongs to the family of growth-associated proteins, which also includes GAP-43, a protein recently shown to regulate neural cell adhesion molecule (NCAM)-mediated neurite outgrowth. Here, the effects of BASP1 overexpression were investigated in PC12E2 cells and primary hippocampal neurons. BASP1 overexpression stimulated neurite outgrowth in both cell types. The effects of BASP1 and trans-homophilic NCAM interactions were additive, and BASP1-induced neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 54 publications
2
71
0
Order By: Relevance
“…The data here indicate a significant reduction in brain acid soluble protein 1 (BASP1) in the cortex following cuprizone treatment. As BASP1 plays a role in neurite growth [29], its loss may potentially be related to axonal damage that has been reported in this model as well as the later stages of clinical MS. Furthermore, neurocalcin was no longer detected in the cortex proteome following cuprizone treatment.…”
Section: Discussionmentioning
confidence: 63%
“…The data here indicate a significant reduction in brain acid soluble protein 1 (BASP1) in the cortex following cuprizone treatment. As BASP1 plays a role in neurite growth [29], its loss may potentially be related to axonal damage that has been reported in this model as well as the later stages of clinical MS. Furthermore, neurocalcin was no longer detected in the cortex proteome following cuprizone treatment.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, we identified three novel miR-7 target genes that are upregulated in gastric cancers in an inflammation-dependent manner. LPHN2 is a G protein-coupled receptor that binds a-latrotoxin (Ichtchenko et al, 1999), whereas BASP1 is implicated in neurite outgrowth (Korshunova et al, 2008). MAFG is one of the small Maf proteins that is important for antioxidant responses (Katsuoka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BASP1 and VIME are proteins implicated in the maintenance of the cell integrity and the stabilisation of the cytoskeletal interactions (Goldman et al 1996, Korshunova et al 2008; as such, they play roles in adhesion, migration, survival and cell signalling. HNRPC is a nuclear pre-mRNA binding protein that has also been implicated in cell proliferation (Kim et al 2003, Schepens et al 2007) and DPY30 is a protein involved in differentiation (Jiang et al 2011).…”
Section: Proliferation and Differentiationmentioning
confidence: 99%